Succinate: a metabolic signal in inflammation - O'NEILL, LUKE (My University, 2013)
Succinate is an intermediate of the tricarboxylic acid (TCA) cycle, and plays a crucial role in adenosine triphosphate (ATP) generation in mitochondria. Recently, new roles for succinate outside metabolism have emerged. Succinate stabilizes the transcription factor hypoxia-inducible factor-1? (HIF-1?) in specific tumors and in activated macrophages, and stimulates dendritic cells via its receptor succinate receptor 1. Furthermore, succinate has been shown to post-translationally modify proteins. This expanding repertoire of functions for succinate suggests a broader role in cellular activation. We review the new roles of succinate and draw parallels to other metabolites such as NAD+ and citrate whose roles have expanded beyond metabolism and into signaling
IN_PRESS
Keywords: metabolism; succinate; inflammation; SUCNR1; HIF-1?; succinylation; Immunology, Inflammation & Infection